Franco-Yugoslav relations in the coverage of the French press in 1934 - Kniazheva E. O. (Interactive science, 2018)
franco-Yugoslav relations are a topic that has so far been little studied in modern Russian historiography. In the Soviet era this issue was given attention only in connection with the attempts of France to create a system of collective security in Europe from the aggression of the revisionist countries, and also in connection with the beginning of cooperation between the countries of the Lesser and Balkan Entente with the USSR. However, in the work the author focused directly on the bilateral cooperation of the two states, which explains not only the policy issues of the 1930s, but also is the key to understanding some of the processes of our time. Bilateral relations of states in the model of «mentor – student», the problem of the importance of the individual in history, and, finally, the problem of the role of the government's dialogue with the public through the media regarding the issues of foreign policy vector.
Keywords: франко-югославские отношения; Марсельское убийство; Третья Республика; Королевство Югославия; Franco-Yugoslav relations; the Marseilles murder; the French press of 1934; the Third Republic; the Kingdom of Yugoslavia; французская пресса 1934 года